Regulatory T Cells Modulate DNA Vaccine Immunogenicity at Early Time via Functional CD4+ T Cells and Antigen Duration - Qin, Lizeng; Jiang, Guosheng; Han, Jinxiang; Letvin, Norman L. (Frontiers in Immunology, 2015)
The development of an effective vaccine against HIV has proved to be difficult. Many factors including natural regulatory T cells (Treg cells), can dampen the CD8 T cell immunogenicity. In this study, we aimed to understand how Treg cells control CD8+ T cell immune responses during DNA prime-boost immunization. Animals were immunized with plasmid HIV IIIB gp120 DNA following elimination of Treg cells by administration of anti-CD25 neutralizing antibody. Results demonstrated that the pool size of CD4+T cells producing both IL-2 and/or IFN-γ (CD4+/IL-2+/IFN-γ+) was increased solely during the priming phase. An increment of tetramer binding and intracellular cytokine IFN-γ expression however were elevated in both primary and secondary stages in CD8+ T cells. The speed of antigen clearance was also investigated by using DNA-luciferase. Surprisingly, DNA luciferase expression was declined to basal level over the ensuing observation period when Treg cells were depleted. Importantly, we found for the first time that DNA expression pattern in Treg-depleted animals was similar to that of the regular memory phase. Moreover, in mice that were exposed to antigen over 5 days prior to Treg cell depletion, CD8+T cell memory response was not affected. Thus, in the present study, we propose a new concept and prove that the enhanced immune response following the depletion of Treg cells during the priming phase likely adds one more set of memory response to the immune system. Taken together, our findings support the notion that Treg cells control DNA vaccine immunogenicity at an early time via antigen duration and functional CD4+ T cell responses.